2014
DOI: 10.1155/2014/861084
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Selected Medicinal Plants against Hydrogen Peroxide Induced Oxidative Damage on Biological Substrates

Abstract: Oxidative stress is developed due to susceptibility of biological substrates to oxidation by generation of free radicals. In degenerative diseases, oxidative stress level can be reduced by antioxidants which neutralize free radicals. Primary objective of this work was to screen four medicinal plants, namely, Andrographis paniculata, Costus speciosus, Canthium parviflorum, and Abrus precatorius, for their antioxidant property using two biological substrates-RBC and microsomes. The antioxidative ability of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In cholesterol, the antioxidant activity of CS Aq at higher concentration was 73.75% which is higher than the methanol extracts (Pai Kotebagilu et al, 2015). This protective action of CS Aq may be contributed to the water soluble phytochemicals such as vitamin C, polyphenols, glutathione and tannins (Pai Kotebagilu et al, 2014). Various studies have reported anti-helminthic and larvicidal activity of aqueous extract of CS leaves (Srivastava et al, 2013;Kanakkanath et al, 2013).…”
Section: Antioxidant Activity Of Andrographis Paniculata (Burmf) Wamentioning
confidence: 94%
See 2 more Smart Citations
“…In cholesterol, the antioxidant activity of CS Aq at higher concentration was 73.75% which is higher than the methanol extracts (Pai Kotebagilu et al, 2015). This protective action of CS Aq may be contributed to the water soluble phytochemicals such as vitamin C, polyphenols, glutathione and tannins (Pai Kotebagilu et al, 2014). Various studies have reported anti-helminthic and larvicidal activity of aqueous extract of CS leaves (Srivastava et al, 2013;Kanakkanath et al, 2013).…”
Section: Antioxidant Activity Of Andrographis Paniculata (Burmf) Wamentioning
confidence: 94%
“…The antioxidant effect of these medicinal plants in biological substrates such as microsomes, red blood cells (Pai Kotebagilu et al, 2014) and lipid substrates such as cholesterol, low density lipoprotein and brain homogenate was evaluated and positive results were obtained (Pai Kotebagilu et al, 2015). This study was conducted in continuation with our previously published work (Pai Kotebagilu et al, 2015) with the major objective of evaluating the antioxidant activity, using aqueous extracts of the AnP, CS, CP and AP.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A large amount of secondary metabolites are present in medicinal plants. Flavonoids, saponins and polyphenols in plants are a versatile group of antioxidants that protect against damage caused due to lipid peroxidation by directly neutralizing reactive oxygen species [15][16][17][18][19][20][21][22]. It is therefore important to study the effect of secondary metabolites on a particular tissue.…”
Section: Introductionmentioning
confidence: 99%
“…It was rated as third plant with potent antioxidant effect among eighteen commonly used antioxidant plants (Lee et al 2015). It is also reported to reduce hydrogen peroxide induced oxidative damage on biological substrates (Pai Kotebagilu et al 2014) and also prevent development of cancer due to its antioxidant action (Baskar et al 2012). The antioxidant effect of this plant is directly related to its phenolic contents (Vijayalakshmi and Sarada 2008;Nehete et al 2010).…”
Section: Introductionmentioning
confidence: 99%